Pelestarian Tari Piriang Diateh Karambie Di Payo Kelurahan Tanah Garam Kecamatan Lubuk Sikarah Kota Solok - Ikrar Dinata; Nerosti Nerosti (FBS Universitas Negeri Padang, 2020)
This study aims to preserve a dance called Tari Piriang on Karambie in Payo, Tanah Garam Village, Lubuk Sikarah District, Solok City. This is a qualitative research with a descriptive method. The object of this research is Tari Piriang on Karambie and is focused on its preservation. The data were collected through field observations, interviews, and documentation done by using cameras. Triangulation technique was used to validate the data. It was conducted by comparing the data from observation tothose from interview and documentation. The results show that (1) Tari Piriang on Karambie, which was founded by Rabaim Pandeka Mudo, was found in Payo, Tanah Garam Village, Lubuk Sikarah District, Solok City. (2) The form of Tari Piriang Diateh Karambie still uses the old movement without being recreated. (3) In term of description of Tari Piriang on Karambiein Payo, Tanah Garam Village, Lubuk Sikarah District, Solok City, there are 7 movements namely Pasambahan, Cincang Pambuka Main, Barabah Mandi, Ramo-Ramo Bagaluik, Sairiang Salangkah, Tuduang Daun and Simpie Nan Ampek. The position of the dancers is not certainly determined when moving on the Karambie (coconut) so that the dancers do not panic looking for the positions while dancing on it. The numbers of dancers are 4 to 8 in maximum. (4) The training of Tari Piriang on Karambie in Payo, Tanah Garam Village, Solok City, is conducted 4 times, and the researcheruses teacher-to-student teaching method. The researcher exemplifies the movements and the dancers does the movements taught by the theresearcher. (5) The dancers of Tari Piriang on Karambie wear uniforms, and the dance is accompanied by musical instruments such as Talempong, Gendang, Giring-giring, and recorders. This is successfully performed at Syek Kukut Park in Solok city. Thus, the researcher concludes that preserving Tari Piriang on Karambie has a good impact on the continuity of culture in Payo, Tanah Garam Village, Lubuk Sikarah District, Solok City.